Analysis of Effect of Science Instructional Materials on Students’ Academic Performance in Ilorin West, Kwara State - Abidoye, Florence Omosholape; Abidoye, Adekunle Omotayo (EduBasic Journal: Jurnal Pendidikan Dasar, 2023)
This study examined the analysis of the effect of science instructional materials on students’ academic performance in Ilorin West, Kwara State. Three research questions were formulated while two hypotheses were tested for the study. The study was descriptive research of the survey type. It was targeted at science students in various schools in Ilorin West, Kwara State, Nigeria. A random sampling technique was used to select 120 science students from various schools in Ilorin West LGA, Kwara State, Nigeria. The research-designed questionnaire was used to accumulate information about class size, school type, and academic performance from respondents. The data accumulated was analyzed using frequency count and percentage, mean, and standard deviation while the research hypotheses were analyzed using an independent t-test and ANOVA. Findings from the study revealed that science instructional materials have a great effect on various school students’ academic performance. The students taught with science instructional materials have excellent performance compared to those taught without the science instructional material. There was also a significant effect based on school type while there was no significant effect based on class size. Recommendations made based on this result were that the Ministry of Education should take responsibility for providing science instructional materials to broader schools to enhance better performance in science around the state.